Dominant leg strength and proficiency in cross-country skiing - Cetin, E. (The Journal of Physical Fitness and Sports Medicine, 2013)
The purpose of this study was to determine the effect of cross-country skiing training on dominant leg strength. The study included fifteen junior and twelve youth cross country skiers, and fourteen sedentary male volunteers. Test data were obtained from Cybex II Norm isokinetic strength measurement equipment. Statistical analysis was conducted using the Wilcoxon matched pairs test. Strength was determined at the 60°/sec (Isokinetic Speed 60°/sec Reps 5) and the 180°/sec (Isokinetic Speed 180°/sec Reps 20). Junior cross-country skiers did not have any significant difference for peak torque and ratio between legs (p<0.05). However, youth athletes and the control group had significant side differences in both quadriceps and hamstring muscle strength. Only the junior group did not have any significant ratio difference at 60°/sec, whereas only the control group had a significant ratio difference at 180°/sec between sides (p<0.05). According to the results of this study, there was no significant difference between right and left leg strength of the quadriceps (Q) and hamstrings (H), and Q/H ratios of junior cross country skiers (p<0.05).